2010
DOI: 10.1111/j.1365-2958.2009.06997.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport-dependent endocytosis and turnover of a uric acid-xanthine permease

Abstract: SummaryIn this work we unmask a novel downregulation mechanism of the uric acid/xanthine transporter UapA, the prototype member of the ubiquitous Nucleobase-Ascorbate Transporter family, directly related to its function. In the presence of substrates, UapA is endocytosed, sorted into the multivesicular body pathway and degraded in vacuoles. Substrateinduced endocytosis, unlike ammonium-induced turnover, is absolutely dependent on UapA activity and several lines of evidence showed that the signal for increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
143
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(153 citation statements)
references
References 61 publications
10
143
0
Order By: Relevance
“…This is reminiscent of what happens with the uric acid and xanthine permease (UapA) of A. nidulans, which undergoes ubiquitylation and endocytosis in response to Am but also to transport of its substrates (24). Substrate transport-induced endocytosis has also been demonstrated in the case of Fur4, the yeast uracil permease (23,25).…”
Section: Cen-ars Gal1-gap1-167(k9r-k16r)-gfp (Ura3)mentioning
confidence: 96%
See 1 more Smart Citation
“…This is reminiscent of what happens with the uric acid and xanthine permease (UapA) of A. nidulans, which undergoes ubiquitylation and endocytosis in response to Am but also to transport of its substrates (24). Substrate transport-induced endocytosis has also been demonstrated in the case of Fur4, the yeast uracil permease (23,25).…”
Section: Cen-ars Gal1-gap1-167(k9r-k16r)-gfp (Ura3)mentioning
confidence: 96%
“…Still, it remains to be determined whether the signal inducing the endocytosis of these yAAPs is the internal accumulation of the transported amino acid (e.g., inhibiting the Npr1 kinase and thereby activating arrestin-like adaptors) or the catalytic process of amino acid transport itself. That transport catalysis might induce the Ub-dependent endocytosis of specific yAAPs is conceivable, as such a mechanism has been described for at least two fungal permeases, the uracil permease Fur4 (23) and the uric acid/xanthine permease UapA of Aspergillus nidulans (24). Recent work suggests that uracil-induced ubiquitylation of Fur4 is due to a conformational change causing disruption of an interaction between the membrane-proximal N-terminal tail and internal loops of the permease, thereby rendering N-terminal lysines more accessible to ubiquitylation by Rsp5 (25).…”
mentioning
confidence: 99%
“…Epifluorescence Microscopy-Samples were prepared as previously described (55,56). 20 mM L-proline was used for induction of prnB expression, at 25°C for 12-14 h. Samples were observed using a Plan-Apochromat ϫ100 1.40 NA oil immersion objective lens on an Axioplan 2 fluorescence microscope (Carl Zeiss, Inc.) with appropriate filters and the resulting images were acquired with a Zeiss-MRC5 digital camera using AxioVs40 V4.…”
Section: Methodsmentioning
confidence: 99%
“…Protein Extraction and In-gel Fluorescence-Membrane-enriched protein extracts were prepared as previously described (22,55), with the following modifications (58). Following membrane protein precipitation by centrifugation (1 h, 18,000 ϫ g, 4°C), the extraction buffer was removed and the pellet was resuspended in ice-cold In-gel Fluorescence Resuspension Buffer (IFRB: 50 mM Tris-HCl, pH 7.5, 5 mM EDTA, 10% glycerol) freshly supplemented with protease inhibitor mixture (Sigma, P8215, 1:500) and 1 mM PMSF.…”
Section: Methodsmentioning
confidence: 99%
“…Load-and-chase experiments have shown that when the dye FM4-64 is endocytosed, it first appears in cortical punctate structures (36). Active research concerning membrane proteins (see reference 12 for a review), determination and maintenance of polarity during development (including the possible involvement of sphingolipids [23], which may be involved in signaling eisosomal protein phosphorylation in S. cerevisiae), and ongoing recent work on endocytosis (1,5,6,16,36,40) make A. nidulans an obvious model within the Pezizomycotina with which to study eisosomal presence, structure, and function. A description of the presence and fate of these organelles during asexual development is presented below.…”
mentioning
confidence: 99%